Optimization of Anti - Erosion Structure of Gas Transmission Elbow Based on Numerical Simulation - WU Li - juan, XIANG Fei, SHI Bao - cheng, ZHANG Yin - di, ZHANG Xing - kai, ZHAI Xiao - peng, LOU Yi - shan (Cailiao Baohu, 2021)
It is inevitable for the natural gas extracted from gas wells to carry solid impurities, which will cause erosion damage to the gas gathering pipeline, especially at the elbow. On the basis of the existing erosion laws of elbows, in order to find out the erosion morphology more intuitively and improve the erosion resistance of elbows in a targeted manner, a numerical simulation study on the erosion laws of conventional gas transmission elbows was conducted. Discrete Phase Model (DPM) was used to simulate the movement of discrete particles, and the erosion and wear prediction model proposed by Tulsa University (E/CRC) was selected. Additionally, the reliability of the model was verified by comparison with experiments. According to the feature that erosion wear mainly occurs at 45°～55°of the elbow, three kinds of optimized elbow structures including gradually expanding elbow, suddenly expanding elbow and elbow with deflector were designed to slow down the erosion and wear of the elbow. Results showed that compared with the equal diameter elbow, the maximum erosion rate of the gradually expanding elbow and the elbow with deflector under the same operating conditions was reduced by 64% and 34% respectively, while the sudden expanding elbow would aggravate the erosion at the elbow. In general, the conclusion could provide a theoretical basis for the optimization of the anti - erosion structure of the elbow.